Peran Guru Agama Hindu dalam Masyarakat Hindu di Kecamatan Balai Riam - Mardwiatmoko, Mardwiatmoko (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
The purpose of this study is to find out the role of Hindu teachers who live in Balai Riam District, Sukamara Regency, Central Kalimantan in religious life in this region. This research is an urgency carried out to foster awareness for Hindu teachers at the research site to devote themselves to the community so as to accelerate the realization of a religious Hindu community. The researcher chose the location of this study because there are a large number of Hindu teachers, but this area has not shown as a religious Hindu community. This type of research is qualitative research with a descriptive approach. The primary data of this study was obtained through interviews and observations. Secondary data were obtained through data documentation relevant to the focus of this study. The findings of this study are that Hindus in Balai Riam District have not fully understood the concepts of Hindu teachings. Not all Hindu teachers want to play a role in realizing a religious Hindu society. The form of contribution of some Hindu teachers to Hindus is as the organizer of religious activities in the temple and assists in the implementation of yajna ceremonies organized by Hindus. As well as acting as the main initiator of the establishment of Widya Bhakti Temple and Indraprastha Temple, and as a dharma pracaraka in the development of Hindus.